2022
DOI: 10.1021/acsearthspacechem.2c00068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Matrices on Nucleophilic Aqueous Aerosol Chemistry: Yields and Mechanistic Insight for Brown Carbon Formation from Glyoxal and Ammonia

Abstract: Climate forcing effects of tropospheric aerosols are determined by their relative abilities to absorb and scatter light and also their effects on cloud properties and lifetime, which may lead to net warming or cooling of the atmosphere. Many details of the formation and lifecycle of organic content that contributes to aerosol light absorption, termed brown carbon (BrC), remain uncertain after extensive study. The reactive species that form BrC make up only a small fraction of total aerosol organic content, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In particular, the pericyclic compound (IM7) is derived from the amine intermediates (IM1 and IM2 or IM4 and GLY monohydrate). The interaction between the two monosubstituted amines of IM1 and IM2 (ΔG ‡ = 6.06 Bi-imidazole 22,36,40 and oxazole species 9 have been found to form in the evaporating and evaporated glyoxal-(NH 4 ) 2 SO 4 droplets. Hence, we examined the formation mechanism of biimidazole and oxazole species.…”
Section: Formation Of Imidazole and Its Derivatives Fig 2 Illustratesmentioning
confidence: 99%
“…In particular, the pericyclic compound (IM7) is derived from the amine intermediates (IM1 and IM2 or IM4 and GLY monohydrate). The interaction between the two monosubstituted amines of IM1 and IM2 (ΔG ‡ = 6.06 Bi-imidazole 22,36,40 and oxazole species 9 have been found to form in the evaporating and evaporated glyoxal-(NH 4 ) 2 SO 4 droplets. Hence, we examined the formation mechanism of biimidazole and oxazole species.…”
Section: Formation Of Imidazole and Its Derivatives Fig 2 Illustratesmentioning
confidence: 99%
“…In the reaction of glyoxal and ammonium, BI is one of the major secondary products formed. 41 The BI yield from the GL + AS reaction was measured at 3 M AS and varying GL concentrations and found to range from ca. 50 to 200 μM.…”
Section: Atmospheric Sinks Of Gl + As Brcmentioning
confidence: 99%
“…Based on the fluorescence intensities of the GL + AS BrC samples and neat BI, we estimate the yields to be on the order of 50 μM in the synthetic conditions used here. Recent work has also shown that matrix effects such as the addition of organics like acetic acid and acetone can increase the yield of these secondary products and promote further BI formation . Therefore, the formation of BI is an important consequence of the reaction of dicarbonyls and ammonium in the atmosphere and BI is likely a significant component of aerosols and cloud water.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,11,12 Furthermore, some carbonyl compounds such as glyoxal are precursors for Brown Carbon (BrC) formation. [13][14][15][16][17] Despite the abundance of carbonyl compounds in the atmosphere, for the most part, heterogeneous and multiphase reactions of these compounds on mineral surfaces were considered insignicant due to their volatility. 12 MEK is the second most abundant atmospheric carbonyl compound aer acetone, 11,18 with a typical mixing ratio of 0.03-4 ppb.…”
Section: Introductionmentioning
confidence: 99%